Disease Pattern of Hospitalization in 198 Hospital in 2019 according to the ICD-10 System - Thanh Tung, Nguyen; Van Hien, Nguyen; Thi My An, Nguyen; Dang Tuan, Mac (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
This study aims to illustrate the disease module of a number of patients who were treated in inpatient departments in 198 Hospital in 2019. The study used the retrospective description of the inpatients’ retrospective data from case reports in the named hospital from 1 st January 2019 to 31 st December 2019. The results show that most inpatients were freelancers (33.89%) and retired people (25.81%). The proportion of elder people in the over-60 age group was the highest - 34.34%, whereas that of under-20 age group was the lowest - 2.91%. The most popular inpatient department was the Center for High Quality Health Care Services - 3.08%. The Hematology-blood Transfusion Center had the smallest number of inpatients (1.39%). The disease module shows that the percentage of inpatients who had diseases of circulation system led the way with 12.38%, followed by the groups of patients who had infectious and parasitic diseases (12.07%). Musculoskeletal-joint and connective tissue diseases, and gastrointestinal diseases took the third and fourth places with the rates of 10.54% and 9.70%, respectively. The least common chapters in this disease module according to ICD-10 system were congenital malformations, deformations and chromosomal abnormalities; and Codes for special purposes, estimated at 0.09% and 0%, respectively. External causes of morbidity and mortality, and mental and behavior disorders also belonged to the lowest common diseases groups, with 0.18% and 0.63%, respectively. Overall, most of the inpatients were elder people, working as freelancers or retired at hospitalization. Inpatients commonly received treatment due to diseases of circulation system or infectious and parasitic diseases. The proportions of digestive diseases, and infectious and parasitic diseases groups were large and similar across the age groups. Keywords Disease pattern, hospitalization, ICD-10, References [1] P. Q. Cu, Research on Disease Models and Solutions to Manage and Improve the Health of Officers and Soldiers of the People's Police. Scientific Project of the Ministry of Public Security, 2012, pp. 88-91 (in Vietnamese). [2] D. Y. Na et al, Research on Disease Structure of Soldiers and Soldiers treated at 19-8 Hospital - Ministry of Public Security, Ministerial-level Scientific Research Project, Hanoi, 2004, pp. 47-51 (in Vietnamese). [3] D. X. Sang, Disease Model of Police Patients Inpatient Treatment at 19-8 Hospital, Master's Thesis of Medicine, Hanoi, Military Medical Academy, 2005, pp. 57-59 (in Vietnamese). [4] P. T. Ngoc, Research on Disease and Accident Injury Models of Patients Who are Police Inpatients at 19-8 Hospital in 2011, Master's thesis on Hospital Management, Hanoi University of Public Health, 2011, pp 61-65 (in Vietnamese). [5] Ministry of Health and Institute of Information Technology – Central Medical Library, Health Statistics, Hanoi, 2012 (in Vietnamese).